Interrelasi Intelektual antara Universitas Al-Azhar Kairo dengan Pondok Modern Gontor (Studi Analisis Kurikulum KMI di Pondok Modern Darussalam Gontor) - Aida Arini (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2017)
Al-Azhar Kairo is a symbol of Islamic progress many generations, which Al-Azhar Kairo is an Islamic educational institution that is able to create ulama'-scholars, jurists', students which are able to contribute to Islamic education, especially education of pesantren in Indonesia. Various schools in Indonesia actually have the characteristics of the different education and learning. The characteristics of education and learning in pesantren prove from the ideas and concepts of the leaders and administrators of the cottage. In this case, the head of the cottage PMDG as well several cadres of pesantren have scientific background of the University of Al-Azhar Kairo. Thus directly or indirectly, the process of transformation of philosophy and scientific values ​​occur through programs and activities of the cottage, particularly programs and curriculum activities at KMI. The research problems are: 1. What is the pattern of relations between Al-Azhar Kairo and Pondok Modern Darussalam Gontor. 2. What forms of intellectual interrelation alumni of Al-Azhar Kairo in curriculum development in Pondok Modern Darussalam Gontor. This study uses field research, qualitative descriptive research approach. To analyze the data,the researcher uses data reduction data presentation and verification of data. The researcher collects the data using interviews, observation and documentation. Based on the research results, it can be concluded as follows: 1. The patterns of relationship between Pondok Modern Darussalam Gontor and Al-Azhar Kairo is the pattern of socio-intellectual that with their experience of traveling overseas, cottage cadre delegation to continue the study and a cadre delegation cottage coaching preachers-preachers in the world, as well as its cooperation in the field of education, both with moral and material support. 2. The form and the process of transformation is done interrelation of Intellectual alumni of Al-Azhar Kairo in curriculum development Pondok Modern Darussalam Gontor, either directly or indirectly lead to the development of language, curriculum development and teaching materials development, with reference to some of the works and literature classic of Al-Azhar Kairo in learning activities